Genetic relatidness and In vitro antimicrobial activities of alkaloids isolated from Indian varieties of Catharanthus roseus (L.) - S, Vardhan; Yadav, A K; Suri, R K; Nag, B.B.S.P (Current Botany, 2012)
Catharanthus roseus (L.) is one of the most intensively studied for its anticancerous property but phytopathogenic activity of the plant has not been much studied. Callus induction from C. roseus was optimized by varying various harmone concentrations and the best result was obtanined in MS medium fortified with 2mgL-1 2, 4-D and 0.1 mgL-1 kinetin. Antimicrobial activity and minimum inhibitory concentration showed that the 20, 40, and 80% leaves, shoot, and root extract inhibits Gram positive B. subtilis and phytopathogenic fungus F. oxysporium, A. niger, Rhizoctonia solani, Colletotrichum falcatum, Cylindrocladium scoparium respectively. Genetic relatidness was determined by RAPD analysis revealed that, white and violet colored C.roseus flowered plant was closely related than rosy pink coloured flower.